Current understanding of thalamic structure and function in migraine. (November 2019) - Younis, Samaira; Hougaard, Anders; Noseda, Rodrigo; Ashina, Messoud
Objective: To review and discuss the literature on the role of thalamic structure and function in migraine. Discussion: The thalamus holds an important position in our understanding of allodynia, central sensitization and photophobia in migraine. Structural and functional findings suggest abnormal functional connectivity between the thalamus and various cortical regions pointing towards an altered pain processing in migraine. Pharmacological nociceptive modulation suggests that the thalamus is a potential drug target. Conclusion: A critical role for the thalamus in migraine-related allodynia and photophobia is well established. Additionally, the thalamus is most likely involved in the dysfunctional pain modulation and processing in migraine, but further research is needed to clarify the exact clinical implications of these findings.